2016
DOI: 10.1016/j.neurobiolaging.2016.07.004
|View full text |Cite
|
Sign up to set email alerts
|

The presence of heterogeneous nuclear ribonucleoproteins in frontotemporal lobar degeneration with FUS-positive inclusions

Abstract: Frontotemporal lobar degeneration with fused in sarcoma-positive inclusions (FTLD-FUS) is a disease with unknown cause. Transportin 1 is abundantly found in FUS-positive inclusions and responsible for the nuclear import of the FET proteins of which FUS is a member. The presence of all FET proteins in pathological inclusions suggests a disturbance of transportin 1-mediated nuclear import. FUS also belongs to the heterogeneous nuclear ribonucleoprotein (hnRNP) protein family. We investigated whether hnRNP protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(41 citation statements)
references
References 41 publications
4
37
0
Order By: Relevance
“…No immunoreactive structures, resembling those seen in FTLD cases on tau or TDP-43 immunostaining, were seen following immunostaining for hnRNP A1, A2/B1 or A3, consistent with previous findings [11]. Such observations would be consistent with genetic studies showing that mutations in hnRNP A1 and hnRNP A2/B1 genes, which might be anticipated to result in molecular or pathological changes, are extremely rare events in both FTLD and MND [5, 14, 15, 30].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…No immunoreactive structures, resembling those seen in FTLD cases on tau or TDP-43 immunostaining, were seen following immunostaining for hnRNP A1, A2/B1 or A3, consistent with previous findings [11]. Such observations would be consistent with genetic studies showing that mutations in hnRNP A1 and hnRNP A2/B1 genes, which might be anticipated to result in molecular or pathological changes, are extremely rare events in both FTLD and MND [5, 14, 15, 30].…”
Section: Discussionsupporting
confidence: 92%
“…However, given the wide range of semi-quantitative scores for hnRNP A1 and A2/B1 across each of the pathological groups, the microscopic observations could not be substantiated by semi-quantitative statistical analysis. Nonetheless, Gami-Patel and colleagues also noted an increased cytoplasmic staining of hnRNP A1 in cases with FTLD-FUS [11]. Together, these data suggest there might be a derangement of movement of hnRNP A1, and other hnRNP proteins, across all pathological forms of FTLD beyond that involving just TDP-43 or FUS.…”
Section: Discussionmentioning
confidence: 96%
“…The association between hnRNP E2 and TDP-43 in DN in SD, when taken in conjunction with previous findings showing specific interactions between hnRNP A1 and FUS-positive NCI [12] and hnRNP A3 and DPR in C9orf72 expansion carriers [3, 9, 23, 24], suggests that specific changes in different hnRNPs might underlie each pathological form of FTLD. The exact nature of how these proteins (hnRNP E2, TDP) might interact is outside the scope of the present study and requires further work, employing expression studies, western blotting or pull-down methodologies, for example, to support the present argument that an increase in hnRNP E2 protein in NCI is specific to FTLD-TDP type C.…”
Section: Discussionsupporting
confidence: 81%
“…For example, we [9] and others [3, 23, 24] have shown that hnRNP A3 is present in the aggregates of dipeptide repeat proteins (DPR) in FTLD patients bearing expansions in C9orf72 gene. Elsewhere, Gami-Patel and colleagues reported the presence of various hnRNPs, but especially hnRNP A1, within NCI in patients with the Neuronal Intermediate Filament Inclusion Body Disease form of FTLD-FUS [12]. …”
Section: Introductionmentioning
confidence: 99%
“…In contrast, in cases of ALS-FUS, TAF15 and EWS remain localized to the nucleus and do not label FUS-positive inclusions. Furthermore, in addition to FET proteins, the presence of hnRNP A1 was also found in FUS neuronal cytoplasmic inclusions and dystrophic neurites of patients diagnosed with the very rare neurological disorder known as neuronal intermediate filament inclusion disease (NIFID) [103] and have also been observed in atypical frontotemporal lobar degeneration with ubiquitin-positive inclusions (aFTLD-U) [99]. In keeping with this finding, a direct comparison of the FUS pathology that characterizes the three major FTLD-FUS subtypes (aFTLD-U, NIFID and basophilic inclusion body disease, BIBD) has shown significant similarities but also differences in the morphology of the FUS inclusion of these patients.…”
Section: Specific Tdp-43/fus Alterations In Ftldmentioning
confidence: 99%